PHANTOM LYMB SYNDROME: ANATOMICAL MECHANISMS AND CLINICAL IMPLICATIONS (Modern American Journal of Medical and Health Sciences, 2026)
Phantom Limb Syndrome (PLS) is a complicated condition related to neurology in which individuals continue to perceive sensations, including pain, in a limb that has been amputated. Majority of amputees experience this phenomenon, and it reflects intricate neuroanatomical and neurophysiological adaptations across the peripheral and central nervous systems. It is important to differentiate it from residual limb pain or non-painful phantom phenomena. PLS is not only purely psychological experience, but it also causes various structural and functional changes within the nervous system. Understanding the anatomical mechanisms behind PLS provides insight into neuroplasticity and informs modern pain management strategies.